POLITIK SEKSUAL MAJALAH HAI - Muria Endah Sokowati (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2017)
The power or knowledge relations determine sexuality as a discourse. How understanding and practicing sex is the negotiation of knowledges and interests. It also happens in producing discourse of sexuality to adolescence. The social construction of adolescence as social category that is apolitical, hedonic, passive and uncritical brings them to be the older people’s object of socialization and education about morality. Different social institutions, such as school, family, religion, government, and also media attempt to subjugate adolescense’ passion in the name of sex education. This research has revealed on how the discourse of sexuality becomes arena where interests of some institutuions involved are contesting. Hai magazine is chosen as locus since this magazine has existed more than three decades and presented sex education as the material in its publication. Using Norman Fairclough’s critical discourse analysis, this research has explored the discourse of sexuality as the result of negotiation of the discourse of sex sacralization brought by social and religion norms, the idea of global sexual revolution, and the perspective of health reproduction. It becomes Hai’s survival strategy in economy, social and political context.